2020
DOI: 10.1039/d0ra07322a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of tough, anisotropic, chemical-crosslinker-free poly(vinyl alcohol) nanofibrous cryogels via electrospinning

Abstract: Fabrication of tough, anisotropic, and chemical crosslinker-free nanofibrous cryogels made from poly(vinyl alcohol) and glycerol via electrospinning in conjunction with freeze-thawing treatment which would be favorable for medical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
(42 reference statements)
0
11
0
Order By: Relevance
“…The FT method can produce a non-toxic hydrogel because the synthesis process does not require a chemical cross-linking agent. 38 During the freezing process, the PVA polymer networks form intermolecular and intramolecular hydrogen bonds, as well as crystallites in which the PVA chains aggregate with ice crystals. The GLE in the PVA polymer network can affect the formation of crystallites, resulting in pores in the hydrogel structure.…”
Section: Introductionmentioning
confidence: 99%
“…The FT method can produce a non-toxic hydrogel because the synthesis process does not require a chemical cross-linking agent. 38 During the freezing process, the PVA polymer networks form intermolecular and intramolecular hydrogen bonds, as well as crystallites in which the PVA chains aggregate with ice crystals. The GLE in the PVA polymer network can affect the formation of crystallites, resulting in pores in the hydrogel structure.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, FT cycles improve mechanical strengths and stability. 51,52 In our previous study, we reported the G' (260 AE 20 kPa) and tear strength values (5.9 AE 0.5 N mm À1 ) of the PVA hydrogel used in this study in one FT treatment. 25 As the FT treatment in the present study was also performed once, further improvement in mechanical properties would be expected.…”
Section: Discussionmentioning
confidence: 80%
“…Being more permeable than other porous materials, these fabrics are also suitable for separation applications . Electrospinning is a well-known method for preparing nanofibers, in which a polymer solution is electrified and injected from a spinneret onto a collector. Examples of electrospun nanofibers reported previously as adsorbent materials include poly­(vinylidene fluoride)/graphene oxide, poly­(vinylidene fluoride)/SiO 2 , poly­(styrene) (PS)/superfine powdered activated carbon, and PS/SiO 2 . In all previous studies, the matrix polymer was blended with other compounds to improve the specific surface area and adsorption capacity.…”
Section: Introductionmentioning
confidence: 99%